Generation of vascular chimerism within donor organs - Shahar Cohen (Nature Portfolio, 2021)
Abstract Whole organ perfusion decellularization has been proposed as a promising method to generate non-immunogenic organs from allogeneic and xenogeneic donors. However, the ability to recellularize organ scaffolds with multiple patient-specific cells in a spatially controlled manner remains challenging. Here, we propose that replacing donor endothelial cells alone, while keeping the rest of the organ viable and functional, is more technically feasible, and may offer a significant shortcut in the efforts to engineer transplantable organs. Vascular decellularization was achieved ex vivo, under controlled machine perfusion conditions, in various rat and porcine organs, including the kidneys, liver, lungs, heart, aorta, hind limbs, and pancreas. In addition, vascular decellularization of selected organs was performed in situ, within the donor body, achieving better control over the perfusion process. Human placenta-derived endothelial progenitor cells (EPCs) were used as immunologically-acceptable human cells to repopulate the luminal surface of de-endothelialized aorta (in vitro), kidneys, lungs and hind limbs (ex vivo). This study provides evidence that artificially generating vascular chimerism is feasible and could potentially pave the way for crossing the immunological barrier to xenotransplantation, as well as reducing the immunological burden of allogeneic grafts.